STUDY OF CULTURAL PROPERTIES OF RECOMBINANT LUMPY SKIN DISEASE VIRUSES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This study investigated the cultural (growth) properties of recombinant strains of the lumpy skin disease virus (LSDV) of cattle, developed on the basis of the Dermatitis nodulares/2016/ Atyrau/KZ strain with knockouts of immunomodulatory genes (LSDV005, LSDV008, LSDV066, LSDV142) and insertion of the IL-18 gene. The replicative activity of the viruses was evaluated in LT, MDBK, SK, Vero, and CT cell cultures. All recombinant viruses retained the ability to efficiently replicate in LT and MDBK cells, producing infectious titers comparable to those of the parental strain. The most pronounced reduction in viral infectivity was observed in multi-deletion mutants containing the LSDV066 gene knockout. These results confirm that the lumpy skin disease virus is a promising platform for the development of vector vaccines, demonstrating genetic stability and consistent replication capacity under genetic modifications.
Keywords: lumpy skin disease virus, recombinant viruses, immunomodulatory genes, cell culture, vector vaccines, replication.